Penentuan Remaining Service Life Struktur Conveyor B pada Tambang Batubara PT XYZ - Yodi Kurniawan; Elfida Moralista; Zaenal (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. In the mining industry, mining material transfer activities require tools that are able to move materials effectively and efficiently, including conveyors. conveyors made from carbon steel are prone to corrosion due to environmental influences. As a result, corrosion that occurs can reduce the remaining life of the conveyor. Therefore, corrosion control is necessary in order to prevent the rate of corrosion in the conveyor structure and increase the production of processing of excavation materials. The environmental conditions of the research area had an average rainfall amount of 325.88 mm / year, an average air temperature of 32.68°C/year and an average relative humidity of 90.91%/ year. The study was conducted on a 90-meter-long conveyor structure. Research aims to find out the type of corrosion, corrosion control, corrosion rate and the remaining life of the conveyor structure. The type of corrosion on the conveyor structure is even corrosion. The corrosion control method used is a coating method with a 3 layer system consisting of Seaguard 5000 primary coating, Sherglass FF intermediate coating and Aliphatic Acrylic Modified Polyurethane top coating. Corrosion rates in conveyor structures range from 0.1763 – 0.3013 mm/year. The life of the conveyor structure is 8 years and the remaining life of use ranges from 6.04 - 9.34 years. Thus there are 32% or 8 test points that are predicted not to reach the design age of 15 years. Abstrak. Pada industri pertambangan, kegiatan pemindahan material tambang membutuhkan alat yang mampu memindahkan material secara efektif dan efisien, diantaranya adalah conveyor. Conveyor berbahan dasar baja karbon yang rawan mengalami korosi akibat pengaruh lingkungan. Akibatnya, korosi yang terjadi dapat mengurangi sisa umur pakai conveyor. Oleh karena itu, perlu dilakukannya pengendalian korosi agar dapat mencegah laju korosi pada struktur conveyor dan meningkatkan produksi pengolahan bahan galian. Metodologi penelitian yang digunakan adalah pengukuran pengurangan ketebalan struktur conveyor. Kondisi lingkungan daerah penelitian memiliki jumlah curah hujan rata-rata sebesar 325,88 mm/tahun, temperatur udara rata-rata sebesar 32,68°C/tahun dan kelembaban relatif rata-rata sebesar 90,91%/tahun. Penelitian dilakukan pada struktur conveyor sepanjang 90 meter. Penelitian bertujuan untuk mengetahui jenis korosi, pengendalian korosi, laju korosi dan sisa umur pakai struktur conveyor. Jenis korosi pada struktur conveyor adalah korosi merata. Metode pengendalian korosi yang digunakan yaitu metode coating dengan sistem 3 layer yang terdiri dari primer coating Seaguard 5000, intermediate coating Sherglass FF dan top coating Aliphatic Acrylic Modified Polyurethane. Laju korosi pada struktur conveyor berkisar antara 0,1763 – 0,3013 mm/tahun. Umur pakai struktur conveyor 8 tahun dan sisa umur pakai berkisar antara 6,04 – 9,34 tahun. Dengan demikian terdapat 32% atau 8 test point yang diprediksi tidak mencapai umur desain yaitu 15 tahun.